A Technology Integration Education (Tie) Model: Millennial Preservice Teachers' Motivations about Technological, Pedagogical, and Content Knowledge (Tpack) Competencies. (October 2014) - Holland, Denise D.; Piper, Randy T.
Nobel laureates Schultz (1971) and Becker (1964, 1993) reinvigorated the analysis of education investments. Human capital investments that improve cognitive skills for elementary and secondary students have important economic implications. An interdisciplinary, 12-construct technology integration education (TIE) model was developed. The sample consisted of 33 elementary education majors and 23 secondary education majors. Limited correlational and predictive relationships between the motivation variables and TPACK variables were found. However, the empirical evidence revealed new insights about self-determination motivation theory. Intrinsic motivation had a higher, significant positive correlation than extrinsic motivation with three dependent variables, while extrinsic motivation had a higher, significant positive correlation than intrinsic motivation with two dependent variables. These limited findings suggest that complex, contingent relationships exist between motivation variables and TPACK variables. The TIE model advances a robust research agenda for the interdisciplinary field of microhuman capital investments, which includes the education of Millennial preservice teachers.